2010
DOI: 10.4103/0301-4738.62644
|View full text |Cite
|
Sign up to set email alerts
|

Results of screening for retinopathy of prematurity in a large nursery in Kuwait: Incidence and risk factors

Abstract: Aims:The aim of the study was to report the incidence of retinopathy of prematurity (ROP) and severe ROP and identify the risk factors for their development in a large nursery in Kuwait.Materials and Methods:This was a retrospective, interventional, non-comparative, hospital-based study. Retrospective review of ROP records of premature babies having either birth weight of less than 1501 g or gestational age at birth of 34 weeks or less and born between January 2001 and August 2003.Statistical Analysis:By univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
3
30
2
Order By: Relevance
“…However, these improvements have resulted in an increase in the rate of ROP and its severity at presentation 34. These factors have resulted in a steady rise of central visual deficits and birth defects with ROP and cataract as the more common causes of visual deficits and declining rates of infectious and nutritional causes in Group 1 and 2 countries 35. In Group 3 countries, corneal blindness due to Vitamin A deficiencies, infections, and war-related injuries remain the primary etiology of visual deficits 36…”
Section: Causes Of Childhood Blindness and Visual Impairmentmentioning
confidence: 99%
“…However, these improvements have resulted in an increase in the rate of ROP and its severity at presentation 34. These factors have resulted in a steady rise of central visual deficits and birth defects with ROP and cataract as the more common causes of visual deficits and declining rates of infectious and nutritional causes in Group 1 and 2 countries 35. In Group 3 countries, corneal blindness due to Vitamin A deficiencies, infections, and war-related injuries remain the primary etiology of visual deficits 36…”
Section: Causes Of Childhood Blindness and Visual Impairmentmentioning
confidence: 99%
“…[45614] In our study too, the severe ROP was mainly present in <30 weeks gestation and <1200 g birth weight. All the babies with <1000 g birth were affected (ROP any stage), in our study.…”
Section: Discussionmentioning
confidence: 64%
“…5,19 The incidence of ROP requiring laser treatment in present study was 4.5%which was less than some studies in which incidence was 6.7% and 7.8% respectively. 19,20 The ETROP incidence study 3 reported severe pre threshold ROP in 36.9% and 27% incidence of threshold disease was reported in the CRYO ROP study underlining the continued occurrence of this sight-threatening stage of ROP. 21 Some studies have reported incidence less than 5%.…”
Section: Discussionmentioning
confidence: 99%